Cigarette smoking at the Universidad de Antioquia School of Dentistry and related factors. Medellín, 2012 - Agudelo-Suárez, Andrés Alonso; Yepes-Delgado, Fanny Lucía; Castro-Naranjo, Victoria Patricia; Cano-Restrepo, Carlos Mario; Campuzano-Peláez, Claudia Marcela (Revista Facultad de Odontología Universidad de Antioquia, 2017)
Introduction: the goal of this study was to determine the frequency of cigarette smoking among staff from Universidad de Antioquia School of Dentistry and its related factors. Methods: cross-sectional study by means of a self-completion survey administered to professors, students, and employees. Variables: sociodemographic conditions, characteristics of the habit of smoking, weight and height (BMI), and relations with co-workers and classmates. Regarding smoking cessation, prevalence (P: current use) and experience (E: current/past use) were considered. The description of variables was done separately for women (W) and men (M). The association of experience and prevalence to sex, physical activity, and BMI was studied through logistic regression, calculating crude and adjusted Odds Ratio (ORc and ORa, respectively), with 95% confidence intervals (95% CI). Results: sex was significantly associated with smoking, being higher in men (P: ORa 5.34; IC95% 2.73-10.45 and E: ORa 2.93; IC95% 2.08-4.14). Physical activity also had statistically significant association to prevalence (ORa 5.78; 95% 2.02-16.53). Nearly a quarter of men and 8% of women have considered smoking sometime in their lives (p < 0.0001). In a greater proportion, the surveyed population reported that their co-workers or classmates smoke near them (M: 25%, W: 16%, p = 0,007). More than 75% of smokers of both sexes consider the possibility of quitting the habit, or have tried to do so. Conclusions: the habit of smoking showed differences in terms of sociodemographic factors. Promotion and prevention strategies are needed to encourage healthier lifestyles.